Kemampuan Penalaran Matematis Siswa SMA Dalam Menyelesaikan Masalah Matriks Ditinjau Dari Gaya Kognitif - Siti Aminatin Ayunah; Sripatmi Sripatmi; Eka Kurniawan; Syahrul Azmi (Griya Journal of Mathematics Education and Application, 2022)
This study aims to describe the reasoning ability at eleventh science students class of SMA Negeri 1 Pringgarata on solving matrix problem in terms of field independent dan field dependent cognitive styles, so this research is a descriptive study. Sampling used a non-probability sampling technique with purposive sampling type so that the samples in this study were students of Eleventh Grade Science Class at SMA Negeri 1 Pringgarata in the academic year 2021/2022. Methods of data collection throught the provision of reasoning ability tests and Group Embedded Figures Test (GEFT). The research subjects were six students consisting of one student with high field independent cognitive style, one student with moderate field independent cognitive style, one student with low field independent cognitive style, one student with high field dependent cognitive style, one student with moderate field dependent cognitive style, and one student with low field dependent cognitive style. The results showed that subjects with high field independent cognitive style had moderate reasoning abilities with scores , moderate field independent cognitive style subjects had moderate reasoning abilities with scores , subjects with low field independent cognitive style had high reasoning abilities with scores , subjects with high field dependent cognitive style has high reasoning ability with score , subject with moderate field dependent cognitive style has moderate reasoning ability with score , and subject with low field dependent cognitive style has moderate reasoning ability with score .